Using the ¢-meson to probe the medium created in Au+Au collisons at RHIC - Blyth, Sarah-Louise (Department of Physics, 2024)
[pg 76 is missing] This thesis presents measurements of ¢-meson production and elliptic flow, 1,2, with the aim of probing the characteristics of the medium created in ultra-relativistic nucleus-nucleus collisions. Using the decay channel q;-+ K+ K-, high statistics measurements have been made for ¢-meson production at mid-rapidity in Au+Au collisions at ,.,jsim = 200 GeV using the STAR detector at RHIC. The ¢-meson invariant yields both integrated, and as a function of PT, are presented for a wide range of collision centralities. The transverse momentum distributions exhibit an evolution in shape with decreasing collision centrality from exponential-like to power-law-like, indicating a variation in the relative contributions from competing particle production mechanisms to ¢ production as a function of collision centrality. Measurements of the nuclear modification factor, Rep, for 0-5% central relative to 40-60% and 60-80% central collisions show that binary-scaled ¢-meson production is suppressed in central compared to more peripheral collisions. The baryon-meson scaling of Rep observed for other identified particles is also observed for the ¢-meson through its similarity to the K Rep for 0-5%/40-60% ratio. The scaling appears to break down in the 0- 5%/60-80% case. The centrality dependence of the N ( 0) / N ( ¢) ratios are also presented. The central ratio is consistent up to Pr ;S 4 Ge V / c with expectations from a model in which multistrange hadrons are produced predominantly by recombination of thermal s quarks. In addition, the ¢-meson elliptic flow, v2 (pr ), has been measured in Au+Au collisions at ,.,fsim = 62.4 GeV and 200 GeV and is found to be similar for the two collision energies. The significant v2 for the ¢-meson, comparable to that of other particles, indicates significant rescattering of the medium constituents. In minimum bias collisions at 200 GeV, for PT < 2 GeV /c, the ¢-meson v2 is consistent with a mass ordering expected from hydrodynamics while for PT > 2 Ge V / c it is consistent with meson-scaling. This is strong evidence for partonic collectivity of the medium created in the collisions. First measurements of the centrality dependence of the ¢-meson integrated elliptic flow scaled by the eccentricity of the nuclear overlap region, (v2) / Epart, show an increasing trend with centrality and may indicate greater collectivity of the medium created in central compared to peripheral Au+Au collisions.